A comprehensive analysis of the moist air transonic flow in a nozzle with a very low expansion rate. (25th November 2022) - Wiśniewski, Piotr; Dykas, Sławomir; Majkut, Mirosław; Smołka, Krysian; Nocoń, Michał; Wittmann, Tim; Friedrichs, Jens
Highlights: Experimental study of the moist air transonic flow in a nozzle with a low expansion rate. Mathematical models of homogeneous condensation. The study of the effect of air relative humidity on the expansion process. The study of the interaction between condensation and pressure waves. Abstract: Inevitable and undesirable as it is, phase transition has a significant impact on the fluid flow efficiency in many energy processes. This paper deals with the impact of water vapour condensation and liquid water evaporation in the moist air expansion in a nozzle with a low expansion rate. The presented comprehensive analysis includes a numerical study supported by analytical and experimental research. The experimental study concerning measurements of atmospheric air transonic flows was carried out using an in-house experimental test rig. A nozzle with a low expansion rate of P ̇ ≈ 1000 s - 1 was investigated experimentally at different inlet air relative humidity values included in the range of 25 to 51 %. The nozzle was measured for supersonic outlet conditions, as well as with elevated back pressure (78 kPa). The technique of Schlieren photography and static pressure measurement on the nozzle wall were used for qualitative identification of both condensation and shock waves. The presented numerical modelling was conducted using commercial computational fluid dynamics software extended with an in-house condensation model. The code was validated against experimental data and data available in the literature. The analysis of the flow in the nozzle with a very low expansion rate revealed very interesting structures of pressure waves. The impact of relative air humidity on the condensation process and the interaction of the condensation wave with aerodynamic oblique as well as normal shock waves were investigated. It is observed that the higher the air relative humidity value, the more difficult it is to identify aerodynamically induced oblique shock waves in the flow. Finally, considering that the efficiency drop induced by the phase change can reach up to 10 %, the impact of condensation on the expansion process efficiency is presented.